Arthroscopic Shoulder Biceps Suspensionplasty for Hemiplegic Shoulder Painful Inferior Subluxation - Olivier Bozon, M.D.; Bertrand Coulet, M.D., Ph.D. (Arthroscopy Techniques, 2023)
Inferior glenohumeral subluxation represents one of the causes of disabling pain in patients with hemiplegia after a stroke. In the case of failure of medical treatment by orthosis or electrical stimulation, surgical treatment of suspensionplasty has been described with good results. We describe here an arthroscopic technique of glenohumeral suspensionplasty by tenodesis of the biceps, proposed in the context of a painful glenohumeral subluxation in patients with hemiplegia.